Observational constraints on the origin of the elements: V. NLTE abundance ratios of (Ni/Fe) in Galactic stars and enrichment by sub-Chandrasekhar mass supernovae - Eitner, Philipp; Bergemann, Maria; Ruiter, A. J.; Avril, O.; Seitenzahl, I. R.; Gent, Matthew; Côté, B. (Astronomy and astrophysics, 2023)
Aims. We constrain the role of different Type Ia supernova (SN Ia) channels in the chemical enrichment of the Galaxy by studying the abundances of nickel in Galactic stars. We investigated four different SN Ia sub-classes, including the classical single-degenerate near-Chandrasekhar mass (Mch) SN Ia, the fainter SN Iax systems associated with He accretion from the companion, as well as two sub-Chandrasekhar mass (sub-Mch) SN Ia channels. The latter include the double detonation of a white dwarf accreting helium-rich matter and violent white dwarf mergers.Methods. The chemical abundances in Galactic stars were determined using Gaia eDR3 astrometry and photometry and high-resolution optical spectra. Non-local thermodynamic equilibrium (NLTE) models of Fe and Ni were used in the abundance analysis. We included new delay-time distributions arising from the different SN Ia channels in models of the Galactic chemical evolution, as well as recent yields for core-collapse supernovae and asymptotic giant branch stars. The data-model comparison was performed using a Markov chain Monte Carlo framework that allowed us to explore the entire parameter space allowed by the diversity of explosion mechanisms and the Galactic SN Ia rate, taking the uncertainties of the observed data into account.Results. We show that NLTE effects have a non-negligible impact on the observed [Ni/Fe] ratios in the Galactic stars. The NLTE corrections to Ni abundances are not large, but strictly positive, lifting the [Ni/Fe] ratios by ∼ + 0.15 dex at [Fe/H] −2. We find that the distributions of [Ni/Fe] in LTE and in NLTE are very tight, with a scatter of ≲0.1 dex at all metallicities. This supports earlier work. In LTE, most stars have scaled solar Ni abundances, [Ni/Fe] ≈ 0, with a slight tendency for sub-solar [Ni/Fe] ratios at lower [Fe/H]. In NLTE, however, we find a mild anti-correlation between [Ni/Fe] and metallicity, and slightly elevated [Ni/Fe] ratios at [Fe/H] ≲ −1.0. The NLTE data can be explained by models of the Galactic chemical evolution that are calculated with a substantial fraction, ∼75%, of sub-Mch SN Ia.